The Impact of Perceived Procedural Justice on Dimensions of Customer Citizenship Behaviours: The Mediating Effect of Customer Perceived Support - Ali, Ahmed Hassaan; Song, Jing (Organizations and Markets in Emerging Economies, 2023)
The present study examines the influence of perceived procedural justice (PPJ) on four fundamental dimensions of customer citizenship behaviours (helping other customers, advocacy, customer tolerance, and feedback) and the mediating role of customer perceived support (CPS). Our research setting is the smartphone after-sales service sector in China. Structural equation modeling (SEM) using AMOS is employed to empirically test our hypotheses on the basis of survey data from 368 smartphonecustomers. We find that PPJ significantly contributes to the customer citizenship behaviours of helping other customers, advocacy, and feedback. Surprisingly, we do not find a significant relationship between PPJ and customer tolerance. Our evidence indicates that CPS partially mediates the relationships between PPJ and helping other customers, advocacy, and feedback, but fully mediates the effect of PPJ on customer tolerance. This research contributes to managers’ understanding of how voluntary behaviours can be effectively managed by enhancing PPJ and CPS. Further, it enriches our theoretical understanding of key antecedents of customer citizenship behaviours.
Keywords: perceived procedural justice; customer citizenship behaviours; customer tolerance; customer perceived support; smartphone after-sales service; China